2023
DOI: 10.1111/psyp.14357
|View full text |Cite
|
Sign up to set email alerts
|

Emotional processing and positive affect after acute exercise in healthy older adults

Abstract: The well‐elucidated improvement of mood immediately after exercise in older adults presumably involves adaptations in emotion‐processing brain networks. However, little is known about effects of acute exercise on appetitive and aversive emotion‐related network recruitment in older adults. The purpose of this study was to determine the effect of acute exercise, compared to a seated rest control condition, on pleasant and unpleasant emotion‐related regional activation in healthy older adults. Functional MRI data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…The precuneus is an important hub region of the DMN and is believed to primarily support internally oriented and selfreferential thinking (Northoff et al, 2006). More recently, there was an increasing awareness that the DMN also plays an important role in constructing subjective emotional experiences (Satpute and Lindquist, 2019), and, more specifically, the precuneus has been implicated with emotional regulation strategies via attentional deployment (Ferri et al, 2016;Kommula et al, 2023). On the other hand, DMN functioning was shown to be altered in affective disorders: For example, functional MRI research suggests that major depressive disorder (MDD) in both adults and adolescents is marked by DMN hyperactivity during resting state examination (Ho et al, 2015;Kaiser et al, 2015) and that areas in the DMN are critically involved in rumination (Zhou et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The precuneus is an important hub region of the DMN and is believed to primarily support internally oriented and selfreferential thinking (Northoff et al, 2006). More recently, there was an increasing awareness that the DMN also plays an important role in constructing subjective emotional experiences (Satpute and Lindquist, 2019), and, more specifically, the precuneus has been implicated with emotional regulation strategies via attentional deployment (Ferri et al, 2016;Kommula et al, 2023). On the other hand, DMN functioning was shown to be altered in affective disorders: For example, functional MRI research suggests that major depressive disorder (MDD) in both adults and adolescents is marked by DMN hyperactivity during resting state examination (Ho et al, 2015;Kaiser et al, 2015) and that areas in the DMN are critically involved in rumination (Zhou et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our lab has examined the longitudinal effects of aerobic exercise (three times per week over 6 months) and demonstrated increased positive FC with the left temporal pole, as well as increased anticorrelation between the amygdala and the precuneus over time in the intervention group (Maurer et al, 2022), a region that has been implicated in emotional regulation strategies via attentional deployment (Ferri et al, 2016). While this finding would support long-term adaptations of amygdala-DMN interactions, a recent task fMRI study (Kommula et al, 2023) in older adults also observed a reduced activation of the precuneus region during the visual presentation of positive emotional stimuli after 30 min of a continuous moderate-tovigorous intensity exercise bout. Further, a study in young healthy trained men revealed reduced activity of the precuneus during the presentation of fearful faces after 30 min low-intensity continuous exercise (Schmitt et al, 2019).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, the current study found decreased connectivity between the contralesional ANG and the contralesional supramarginal gyrus outside of DMN in PSD patients. Supramarginal gyrus is a key region for emotional and social processing, 98 , 99 , 100 , 101 and part of the neuroanatomical circuitry for sentence comprehension. 102 Previous studies have demonstrated the impairments of connectivity between supramarginal gyrus and DMN in depressed patients.…”
Section: Discussionmentioning
confidence: 99%